Transcendendo a norma: um diagnóstico da política de cotas para pessoas trans na Universidade Federal do Ceará - Martins, Tatiane Sales (2024)
Trans and transvestite people have historically suffered prejudice and violence since childhood, having to face situations of marginalization that place them in a place where other equally excluded groups are found: the place of minorities. Under these conditions, access to education becomes more difficult, and it is rare to find this group in universities. In view of this, it is necessary to think about public policies that take trans and transvestite people off the streets and out of vulnerable conditions and bring them to the university, so that they can, through education, be in the same spaces and reach the same social positions as the majority. Trans quotas are public affirmative action policies that can help in this process. With the aim of analyzing how the public policy of affirmative action and trans quotas is contemplated at the Federal University of Ceará (UFC), this research makes an analytical-reflexive diagnosis, based on selection notices, regulations, and internal resolutions of the UFC, with regard to trans quotas, showing how this affirmative action is being contemplated at the UFC in terms of its scope, process, and evolution, as well as the apparent deficiencies of this and about this policy at the university. The results of the research show that the UFC is attentive to the movement of inclusion of political minorities in education, offering, based on its autonomy, places for trans people and transvestites in selection notices for master's and doctoral courses, in four of the eighty postgraduate courses. The results also show that the undergraduate courses at the Federal University of Ceará still do not contemplate trans quotas, unlike other Brazilian federal universities located in capital cities. It is concluded that, despite the existence of affirmative action and trans quotas at the University, UFC is still far from its potential, and the results are part of a historical and political situation that leads to the core of the problem of education in Brazil, that is, the exclusion that plagues and crosses time of the politically and humanly minoritized majorities.